Diversity and redundancy of the ripening regulatory networks revealed by the fruitENCODE and the new CRISPR/Cas9 CNR and NOR mutants - Ying Gao; Ning Zhu; Xiaofang Zhu; Meng Wu; Cai-Zhong Jiang; Donald Grierson; Yunbo Luo; Wei Shen; Silin Zhong; Da-Qi Fu; Guiqin Qu (Horticulture Research, 2019)
Fruit ripening: Multiple backup plans The regulatory circuits that govern the expression of genes required for ripening in tomato plants are highly redundant. Fleshy fruits that use the hormone ethylene to regulate ripening have developed independently multiple times in the history of the angiosperms. Guiqin Qu at China Agricultural University in Beijing and colleagues working on the fruitENCODE project are exploring the genetic and epigenetic basis of this convergent evolution. In tomatoes, three transcription factors have been shown to control ethylene production and regulate ripening. However, when gene editing techniques were used to introduce mutations that interfere with the function of these transcription factors, partial ripening or a delay in ripening was observed. The fact that ripening was not abolished indicates that the ripening process is more robust and complex than previously thought.